Technical Limitations of African Prints and their Implications on Garment Construction in Ghana (Journal of Science and Technology, 2016)
African Prints are major raw materials for the Clothing Industry in Ghana. Garment manufacture requires the consideration of technical factors such as alignment of prints to the fabric grain line, standard fabric width, appropriate motif placement/arrangement and repeat pattern among others. As a qualitative enquiry, the study employs descriptive observational research design with observation and interview as the main data collection instruments. The analysis of the study revealed that due to lack of collaboration between the textile and fashion industries, most African prints on the market do not possess the requisite technicalities but rather show weak spots such as limited fabric width, predominant use of full and half-drop pattern layouts, large motifs with intricate textures that pose a greater challenge to the garment designer. Moreover, it was apparent that most local print designs do not follow lengthwise grain of fabric although the grain line is a very important technical consideration in garment construction. The prints, on the other hand, are packaged in six or twelve yards implying that getting the required width will necessitate joining pieces together which is not convenient and amount to a lot of waste during garment construction. The study, among other things, recommends a strong collaboration between textile and fashion designers to ensure that all necessary technical requirements in garment construction are met in the textile design process in order for the two parties to work effectively to meet international standards.